Comparison of transplant outcomes between haploidentical transplantation and single cord blood transplantation in non‐remission acute myeloid leukaemia: A nationwide retrospective study. (25th October 2022) - Matsuda, Kensuke; Konuma, Takaaki; Fuse, Kyoko; Masuko, Masayoshi; Kawamura, Koji; Hirayama, Masahiro; Uchida, Naoyuki; Ikegame, Kazuhiro; Wake, Atsushi; Eto, Tetsuya; Doki, Noriko; Miyakoshi, Shigesaburo; et al.
Summary: Allogeneic haematopoietic stem cell transplantation (HSCT) is a potentially curative treatment for some patients with acute myeloid leukaemia (AML) who are refractory to chemotherapy. Cord blood transplantation (CBT) is a reasonable option in such cases because of its rapid availability. Recently, a growing number of human leucocyte antigen (HLA)‐haploidentical related donor HSCTs (haplo‐HSCTs) have been performed, although its effectiveness remains undetermined. Using the Japanese nationwide transplantation registry data, we identified 2438 patients aged ≥16 years who received CBT or haplo‐HSCT as their first transplant for non‐remission AML between January 2008 and December 2018. After 2:1 propensity score matching, 918 patients in the CBT group and 459 patients in the haplo‐HSCT group were selected. In this matched cohort, no significant difference in overall survival (OS) was observed between the CBT and haplo‐HSCT groups (hazard ratio [HR] of haplo‐HSCT to CBT 1.02, 95% confidence interval [CI] 0.89–1.16). Similarly, no significant difference in the cumulative incidence of relapse (HR 1.09, 95% CI 0.93–1.28) or non‐relapse mortality (HR 0.94, 95% CI 0.76–1.18). Subgroup analysis showed that CBT was significantly associated with preferable OS in patients receiving myeloablative conditioning. Our data showed comparable outcomes between haplo‐HSCT and CBT recipients with non‐remission AML.